Enhanced adsorptive removal of crystal violet dye from aqueous media using citric acid modified red-seaweed: experimental study combined with RSM process optimization. Issue 9 (1st July 2022) - Essekri, Abdelilah; Aarab, Nouh; Hsini, Abdelghani; Ajmal, Zeeshan; Laabd, Mohamed; El Ouardi, Mahmoud; Ait Addi, Abdelaziz; Lakhmiri, Rajae; Albourine, Abdallah
Abstract: Herein, we report the preparation of a novel biosorbent; a citric acid modified red-seaweed for crystal violet (CV) removal from water. Surface characterization and basic biosorption characteristics of pristine red seaweed (RS) and its citric acid-modified form (RS@CA) were critically evaluated through scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Fourier transformed infrared (FTIR) spectroscopy, and BET surface analysis. Batch experiments were, then, performed to evaluate the biosorption performance of adsorbent under various operational parameters. The CV biosorption kinetics and equilibrium data were fitted well by pseudo second order and Langmuir model for both RS and RS@CA, respectively. Optimum monolayer uptakes of RS and RS@CA for CV dye were 142.86 and 217.38 mg g −1, respectively. Thermodynamically, the biosorption process was found to be endothermic (ΔH° > 0) and spontaneous (ΔG° ˂ 0). The CV binding mechanism toward RS@CA surface sites was mainly manifested by the electrostatic driving force pathway. Response surface methodology calculations showed a maximum CV biosorption efficiency of 93.40% at optimum biosorption conditions: pH 7, biosorbent dose of 1.5 g L −1, initial CV concentration of 20 mg L −1, and adsorption time of 90 minutes at 20 °C. The regeneration data further indicated that RS@CA could be effectively reused up to five cycles, losing only 6.7% of the original CV removal efficiency. Finally, it was concluded that RS@CA could be used as a cost-effective, eco-friendly and recyclable biosorbent to remove CV dye from water. Graphical Abstract: UF0001